Measuring the stopping power of α particles in compact bone for BNCT. (29th January 2015) - Provenzano, L; Rodríguez, L M; Fregenal, D; Bernardi, G; Olivares, C; Altieri, S; Bortolussi, S; González, S J
Abstract: The stopping power of α particles in thin films of decalcified sheep femur, in the range of 1.5 to 5.0 MeV incident energy, was measured by transmission of a backscattered beam from a heavy target. Additionally, the film elemental composition was determined by Rutherford Backscattering Spectrometry (RBS). These data will be used to measure boron concentration in thin films of bone using a spectrometry technique developed by the University of Pavia, since the concentration ratio between healthy tissue and tumor is of fundamental importance in Boron Neutron Capture Therapy (BNCT). The present experimental data are compared with numerical simulation results and with tabulated stopping power data of non-decalcified human bone.